Políticas de enfrentamento à lepra/hanseníase em Mato Grosso : do São João dos Lázaros de Cuiabá ao São Julião de Campo Grande (1938-1970) - Heleno Braz do Nascimento (2024)
This thesis analyzes a set of policies to combat leprosy/hansen's disease in Mato Grosso, focusing on the trajectory of Hospital São Julião in the period between 1938 and 1970, with the purpose of answering the following main question: how did the “magnificent” asylum-colony, registered on August 5, 1941, in line with the health agenda to combat the disease defended by the Brazilian State and medical authorities of the period, it ended up becoming a “patient deposit” during the 1960s, especially after the military coup 1964 in Brazil? Its central concern is to give visibility to the transformations that marked the history of the leper colony in the policies to control and combat leprosy/hansen's disease in Mato Grosso during the period in question. To do so, investigate, based on newspapers, magazines, legislation, regulations, administrative documents, interviews and literary works, the different paths taken by São Julião in the development and execution of isolation, prevention, treatment and cure policies for people affected by the disease without a state. Along this path, an asylum institution goes through moments that range from hope to hopelessness; from a “modern” asylum colony to a “ghost town”, a place abandoned by public authorities, marked by various forms of violence and inhabited by individuals stigmatized and “forgotten” by Mato Grosso society. From 1970 onwards, the year in which the administration of the then sanatorium-colony was transferred from the state government to the Association for Aid and Recovery of Leprosy Patients (AARH), the group of volunteers from Operation Mato Grosso (OMG), under the leadership of Sister Silvia Vecellio, began an important process of change in the rumors about leprosy, which became the current Hospital São Julião, a reference in assistance, prevention, treatment, cure and rehabilitation of people affected by hansen's disease.